Content of lunchboxes of Dutch primary school children and their perceptions of alternative healthy school lunch concepts - Frédérique C Rongen; Ellen van Kleef; Monique H Vingerhoeds; Jacob C Seidell; Sanne Coosje Dijkstra (Cambridge University Press, 2023)
Abstract Objective: To investigate the content of lunchboxes of primary school children and to examine children's support and preferences for alternative healthy school lunch concepts. Design: A cross-sectional study among Dutch children from seven primary schools. The content of the lunchboxes was assessed by photographs. Support and preferences for alternative lunch concepts were examined via a self-reported questionnaire. Linear regression analyses were used to investigate the associations between children's support and preferences and sex, educational group and migration background. Setting: The Netherlands. Participants: Primary school children. Results: A total of 660 children were included (average 9·9 years old). Most lunchboxes contained sandwiches and a drink. Few lunchboxes contained fruit or vegetables. The alternative school lunch concepts elicited mixed support among children. The lunch concepts 'Sandwiches prepared by the children themselves' and a 'hot lunch buffet' had the highest mean support, while the concept 'a healthy lunch brought from home' was the most preferred concept. Small significant differences were observed depending on sex, educational group and migration background. Conclusion: Lunchboxes of Dutch children contained sandwiches and a drink but rarely fruit and vegetables. Among different alternatives, children reported the highest support for the preparation of their own sandwiches in class or a hot lunch buffet. Future studies should investigate if these alternative lunch concepts improve the dietary intake of children.